Visioning as an Integral Element to Understanding Indigenous Learners’ Transition to University - Parent, Amy (Canadian Journal of Higher Education, 2017)
This article focuses on high school to university transitions for Indigenous youth at universities in British Columbia, Canada. The study is premised on an Indigenous research design, which utilizes the concept of visioning and a storywork methodology (Archibald, 2008). The results challenge existing institutional and psychological approaches to transitions in revealing that they are deeply impacted by a variety of lived experiences and that a visioning process is vital to Indigenous youths’ participation in university. The paper concludes with implications for practitioners working in educational and Aboriginal community-based settings.